Notes on Contributors - Williams, Quentin (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
Duncan Brown is Professor of English in the Centre for Multilingualism and Diversities Research at the University of the Western Cape. He has published widely in the field of South African literary and cultural studies. His recent books include Wilder Lives: Humans and Our Environments (2019), and Finding My Way: Reflections on South African Literature (2020). He is Principal Investigator on the Andrew W. Mellon funded project on “Rethinking South African Literature(s)” (2019-2024), and Co-ordinator on the South African section of the University of Oslo funded project on “Global Trout: Investigating Environmental Change through More-than-Human World Systems” (2019-2024). Michael Chapman is a researcher-in-residence at the Durban University of Technology in South Africa. His creative nonfictional work Green in Black-and-White Times appeared in 2016. On Literary Attachment in South Africa: Tough Love (2022) seeks to embody in a single language of response two categories that are usually thought to be apart, criticism (conceptual) and art (creative). Andries du Toit is the director of the Institute for Poverty, Land and Agrarian Studies at the University of the Western Cape, where he has spent most of the last thirteen years answering emails and navigating the university's labyrinthine procurement and HR system. In his spare time he does research, focusing on the politics of landlessness, poverty, and inequality in South Africa.